Synthesis and Preconcentration of Amberlite XAD-4 Resin Modified by Dithioethylenediamine - Dolak, Ibrahim; Tegin, Ibrahim; Gⁿzel, Remziye; Ziyadanogullari, Recep (Asian Journal of Chemistry, 2010)
In the present work, Amberlite XAD-4 copolymer resin modified by rubeanic acid was synthesized for separation and preconcentration of Cu(II), Co(II), Ni(II)), Cd (II) and Mn(II). The optimization procedure for analytical parameters including pH, contact time, batch capacity, etc. was examined in order to obtain quantitative recoveries of metal ions. Preconcentration yields of Cu(II), Co(II), Ni(II), Cd (II) and Mn(II) by Amberlite XAD-4-dithioethylenediamine copolymer resin were found as 103.3 ± 2.6, 96.8 ± 1.7, 102.0 ± 3.0, 90.3 ± 1.7 and 97.2 ± 2.4 %, respectively. Batch capacity of Cu(II), Co(II), Ni(II), Cd(II) and Mn(II) by Amberlite XAD-4- dithioethylenediamine copolymer resin was determined as 0.1243 ± 0.0036, 0.2057 ± 0.0034, 0.2323 ± 0.0043, 0.1757 ± 0.0025 and 0.1888 ± 0.0034 mmol g-1 resin, respectively. The preconcentration factor was 500 for Cu (II), Co (II), Ni(II), Cd(II) and Mn(II).